Immunological and Preventive Effects of Hochuekkito and Kakkonto Against Coronavirus Disease in Healthcare Workers: A Retrospective Observational Study - Ogawa-Ochiai, Keiko; Ishikawa, Hideki; Li, Hongyang; Vu Quang, Lam; Kimoto, Izumi; Takamura, Mitsuyuki; Hongawa, Tetsuya; Hane, Yasuyuki; Suzuki, Susumu; Okajima, Masaki; Mori, Keita; Ito, Masanori; et al. (Frontiers in Pharmacology, 2021)
Amid the global outbreak of coronavirus disease 2019 (COVID-19), it may be expected that low-toxicity natural compounds, such as Kampo formulas, will have a preventive effect on COVID-19. Although the biological properties and safety of the representative Kampo compounds, hochuekkito (HET) and kakkonto (KKT), have been confirmed in various animal model experiments, clinical studies, and a few human studies to induce biological effects on various infectious diseases without significant toxicity, it is unclear whether HET and KKT are safe and effective for COVID-19 prevention. The study population included healthcare workers (HCWs), as they are at a higher risk of infection than the other populations. We retrospectively investigated the immunological and preventive effects of HET and KTT against COVID-19. We included 27 HCWs (aged 21-72 years, F:M=18:9) from hospitals and clinics of the Hokuriku-Tokai region. The HCWs received HET and KKT for general fatigue and myalgia during this period for 28 days. We obtained patient clinical data from electronic medical records. We analyzed the changes in immunomodulation before and after the administration of the formulas from residual specimens based on the expression of relevant surface markers. The specimens were also tested for the presence of antibodies against severe acute respiratory syndrome coronavirus 2. The following side effects were reported: abdominal discomfort in five patients, diarrhea in two, and loose or soft stool in three. All 27 HCWs tested negative for COVID-19 antibodies. HET and KKT administration significantly increased the absolute number of circulating lymphocytes expressing the activating receptors NKp46, NKp30, and suppressing receptor NKG2A. There was also a significant increase in the absolute number of circulating lymphocytes expressing the receptors TLR4, OX40, 4–1BB, GITR, PD-1, and ICOS. These data indicate that HET and KKT can enhance and modulate NK activity in circulating human immune cells. The immunomodulatory effects, such as activation and regulation of T cells, are consistent with a putative improvement in infectious immunosurveillance. An increase in the number of T cells and CD4/CD8-positive cells indicates an enhanced ability to protect against infection. HET and KKT may prevent the onset or worsening of COVID-19 through their immunomodulatory effects.